Use of Nanoemulsion-Based Merkubung (Macaranga gigantea) Sap Extract Inhibitor to Improve Corrosion Inhibition Efficiency on Steel - Adetra Febriani Naibaho; Alya Adiningtyas Putri; Dian Natasya; Grescia Angelita Sinaga; Wan Nurul Fadillah; Diah Riski Gusti (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Corrosion frequently affects steel. Although it is an unavoidable natural process, its progression can be managed and its rate reduced. One strategy for mitigating corrosion is the use of corrosion inhibitors. Inhibitors derived from organic sources are widely employed because of their high inhibition efficiency. Sap extract from Merkubung (Macaranga gigantea) can function as a corrosion inhibitor due to the presence of secondary metabolites such as tannins. Tannins are promising corrosion inhibitors since their –OH groups enable them to form complexes with metal surfaces. This study evaluates the performance of a nanoemulsion containing Merkubung sap extract as a steel corrosion inhibitor. The methodology includes extraction, nanoemulsion formulation, and assessment of corrosion rate and inhibition efficiency at various concentrations and temperatures. In this work, nanoemulsion‑based inhibitors were applied to improve corrosion protection of steel. The nanoemulsion demonstrated the lowest corrosion rate (0.902 mg cm⁻² h⁻¹) and the highest inhibition efficiency (66.05 %) at 500 ppm and 30 °C. These results show that the nanoemulsion enhances inhibition performance, making it an effective corrosion inhibitor.